2014 International Conference on the Eleventh Industrial and Commercial Use of Energy 2014
DOI: 10.1109/icue.2014.6904186
|View full text |Cite
|
Sign up to set email alerts
|

Direct current in public lighting for improvement in LED performance and costs

Abstract: Public lighting's primary purpose is nighttime visibility for security and safety. How to meet so many requirements of so many stakeholders? The key to developing a good plan is to relate lighting to functions of public spaces, because street lighting is more than a technical requirement, a security need, or a design element. It can be thought of and utilized in terms of how the type, placement, and wattage affect how a street is perceived and used. With present-day used street lighting systems however, flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Therefore, several Dutch scientists proposed a new technology that combines LED lighting with a Direct Current (DC) power system to improve both performance and costs of LED lights. 103 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several Dutch scientists proposed a new technology that combines LED lighting with a Direct Current (DC) power system to improve both performance and costs of LED lights. 103 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, several Dutch scientists proposed a new technology that combines LED lighting with a Direct Current (DC) power system to improve both performance and costs of LED lights. 103 Interactions between the IEQ factors. Interactions can occur between the different IEQ factors (air quality, thermal quality, acoustical quality and visual quality).…”
Section: Indicatorsmentioning
confidence: 99%
“…The utilization of DC distribution systems for applications such as high voltage distribution [1,2], data centers [2,3], telecommunications [4], commercial [5,6] and residential buildings [7][8][9], and street lighting [10,11] is ever increasing. Moreover, a variety of novel applications, such as microgrids and device level distribution, have recently been identified [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For this paper, we specifically look into the expected energy-efficiency of 350 V DC households compared to 230 AC households [9]. Research has demonstrated: i.…”
Section: Energy Efficiency In Dc-gridsmentioning
confidence: 99%